Morbidade neonatal em um hospital com alta prevalência de cesarianas eletivas - Moraes, Edite Terezinha (2017)
Objectives: To assess the prevalence of neonatal complications requiring special care, respiratory morbidity and hypoxic-ischemic encephalopathy, according to the type of delivery, in a private hospital with a high prevalence of cesarean section. Methods: Retrospective study, involving neonates of ≥37 weeks of gestational age and birthweight of ≥2,500 g whose births occurred between February 2013 and June 2016. Neonates with malformations and/or congenital infections who required special care were excluded. The electronic charts were reviewed by two authors and the data were analyzed using the IBM SPSS version 22.0 program using Chi-square test or Fisher's exact test, Kruskal-Wallis test and Z test. Patients were classified according to type of delivery: vaginal delivery; cesarean section after onset of labor; scheduled cesarean section; cesarean section after rupture of membranes; cesarean section due to specific pathologies or conditions, including maternal hypertensive disease, diabetes, intrauterine growth restriction and twinning; and emergency cesarean section. Subsequently, the types of delivery were reclassified into larger groups for analysis: Group 1: vaginal delivery + cesarean section after labor; Group 2: scheduled cesarean section + cesarean section after rupture of membranes + cesarean section due to pathology. The emergency cesarean section was analyzed separately. Results: A total of 12,528 newborns were included in the study, of which 6,894 (55%) were born by scheduled cesarean section, 3,252 (26%) by other types of cesarean section and 2,382 (19%) by vaginal delivery, resulting in a prevalence of cesarean section of 81%. Fifty-three percent of parturient women were primiparous. Birth weight was significantly higher in scheduled cesarean section than in other types of delivery. The gestational age was not different comparing scheduled cesarean section and vaginal delivery, (median 39 weeks), but was higher in these than in other modes of delivery (median 38 weeks). The need for special care (hospitalization in the Neonatal Intensive Care Unit) in Group 1 was 2.68% (95% confidence interval [CI] 2.06-3.31%) and in Group 2 it was 2.85% (95%CI 2.25-3.21), a non-significant difference (p=0.680). However, analyzing for gestational age, the need for special care in Group 2 was significantly more frequent for those born before 38 weeks (p=0.023) and less frequent for those born after 40 weeks (p=0.026). In the other gestational ages, no significant differences were found between groups. The incidence of early respiratory distress was 0.93% (95%CI 0.56-1.31) in Group 1 and 1.17% in Group 2 (p=0.389). The incidence of hypoxic-ischemic encephalopathy was 0.23% (95%CI 0.05-0.42) in Group 1 and zero in Group 2 (p<0.001). During the study period, there was only one maternal death, in the emergency cesarean section group. Conclusions: A higher prevalence of neonatal morbidity was related to birth before 38 weeks of gestation in the group that included scheduled cesarean section + cesarean section after rupture of membranes + cesarean section due to pathology, compared to the group that included vaginal delivery + intrapartum cesarean section. These results support the recommendations that elective cesareans should be avoided before the 39 completed weeks of gestation. In this sample, cesarean section without previous labor was associated with a reduced risk of hypoxic- ischemic encephalopathy in the neonate.